2017
DOI: 10.1126/scitranslmed.aan8184
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing human monoclonal antibodies prevent Zika virus infection in macaques

Abstract: Therapies to prevent maternal Zika virus (ZIKV) infection and its subsequent fetal developmental complications are urgently required. We isolated three potent ZIKV-neutralizing monoclonal antibodies (nmAbs) from the plasmablasts of a ZIKV-infected patient—SMZAb1, SMZAb2, and SMZAb5—directed against two different domains of the virus. We engineered these nmAbs with Fc LALA mutations that abrogate Fc-gamma receptor (FcγR) binding, thus eliminating potential therapy-mediated antibody-dependent enhancement (ADE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 35 publications
3
79
1
Order By: Relevance
“…An additional possibility is that the animals in the low-dose experiments were only monitored for 7 days, which may not have been sufficient to document delayed infection seen after antibody treatment (Abbink et al, 2018). Whether other antibodies, single or in combination, will be completely protective after high-dose challenge remains to be determined but would be highly relevant for further clinical development, since the precise dose delivered by the Aedes aegypti vector is not known (Abbink et al, 2018; Magnani et al, 2017b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional possibility is that the animals in the low-dose experiments were only monitored for 7 days, which may not have been sufficient to document delayed infection seen after antibody treatment (Abbink et al, 2018). Whether other antibodies, single or in combination, will be completely protective after high-dose challenge remains to be determined but would be highly relevant for further clinical development, since the precise dose delivered by the Aedes aegypti vector is not known (Abbink et al, 2018; Magnani et al, 2017b). …”
Section: Discussionmentioning
confidence: 99%
“…A combination of three antibodies targeting epitopes on the ZIKV envelope domain II and III regions was recently shown to be effective at preventing viremia in macaques (Magnani et al, 2017b), although the same three antibodies in combination failed to prevent virus transmission to the fetus (Magnani et al, 2018). Moreover, it was reported that a single antibody to a conformational epitope prevents ZIKV viremia for 7 days after low-dose challenge (Abbink et al, 2018), but viremia was not evaluated for longer periods of time or upon high-dose viral challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory and others have shown that ZIKV-specific neutralizing antibodies correlate with vaccine protection in both mice and monkeys 36 as well as with rapid control of viremia following infection in monkeys 7 . Several groups have also demonstrated therapeutic efficacy of ZIKV-specific mAbs in immunosuppressed mice 811 , and a cocktail of three ZIKV-specific mAbs that targeted domain III was shown to prevent ZIKV infection in nonhuman primates 12 . In the present study, we assessed the therapeutic and prophylactic efficacy of a potent ZIKV-specific antibody in rhesus monkeys.…”
mentioning
confidence: 99%
“…2). In contrast, a cocktail of three domain III-specific mAbs was required to prevent ZIKV infection in nonhuman primates 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation